Entrepreneurial Management and MSME Performance: The Mediating Role of Digital Innovation - Diah Kusumayanti; Yudin Taqyudin; Mumuh Mulyana (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study examines the role of digital innovation in mediating the relationship between entrepreneurial management and micro, small, and medium enterprise (MSME) performance in an emerging economy context. Although entrepreneurial management has been widely recognized as a key driver of firm competitiveness, empirical evidence on how it translates into superior MSME performance remains inconsistent. Drawing on the Resource-Based View and Dynamic Capability Theory, this study proposes that digital innovation serves as a critical mechanism through which entrepreneurial management creates tangible business value. Using a quantitative explanatory approach, data were collected from 300 MSME owners and managers operating in the trade, service, and manufacturing sectors. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that entrepreneurial management has a significant positive effect on MSME performance and digital innovation. Digital innovation also exerts a strong positive effect on MSME performance. Moreover, the mediation analysis reveals that digital innovation partially mediates the relationship between entrepreneurial management and MSME performance, indicating that entrepreneurial-oriented managerial practices enhance business performance primarily by stimulating digital product, process, and marketing innovations. These findings highlight the importance of integrating entrepreneurial management with digital innovation strategies to improve MSME competitiveness and sustainability. The study contributes to entrepreneurship and innovation literature by positioning entrepreneurial management as a dynamic capability and digital innovation as a key performance mechanism, while offering practical implications for MSME development and digital transformation policies in emerging economies. Keywords: Entrepreneurial management; digital innovation; MSME performance; PLS-SEM; emerging economy; Indonesia.